INTERVENSI PERILAKU LOKAL TERHADAP PEMANFAATAN RUANG PUBLIK - Peggy Egam (EKOTON, 2014)
Human behavior in action shows related to all human activity in the form of physical human interaction with each other or with their physical environment. Humans in the environment is a process of interaction between humans and the environment that involve motivation and needs - the needs of individual and social. Humans both personal and collective has its own uniqueness and karekter. The uniqueness and character naturally inherent or influenced by external faktors such as cultural and physical environment. The uniqueness of every individual will affect the surrounding environment. Conversely, the uniqueness of the environment also affect behavior. because the environment is not just a place for people to move, but also become an integral part of manusia.Pemanfaatan behavior patterns and meaning of public space is often influenced by cultural, ethnic variation, and losasi situational, so that culture is a major modifier penantuan interpersonal distance, local expression that will give meaning and a specific character penggunanan with the local community.